Bacterial and Archaeal α-Amylases: Diversity and Amelioration of the Desirable Characteristics for Industrial Applications - Mehta, Deepika; Satyanarayana, Tulasi (Frontiers in Microbiology, 2016)
Industrial enzyme market has been projected to reach US$ 6.2 billion by 2020. Major reasons for continuous rise in the global sales of microbial enzymes are because of increase in the demand for consumer goods and biofuels. Among major industrial enzymes that find applications in baking, alcohol, detergent and textile industries are α-amylases. These are produced by a variety of microbes, which randomly cleave α-1,4-glycosidic linkages in starch leading to the formation of limit dextrins. α-Amylases from different microbial sources vary in their properties, thus, suit specific applications. This review focuses on the native and recombinant α-amylases from bacteria and archaea, their production and the advancements in the molecular biology, protein engineering and structural studies, which aid in ameliorating their properties to suit the targeted industrial applications.